2013 Eighth International Conference on P2P, Parallel, Grid, Cloud and Internet Computing 2013
DOI: 10.1109/3pgcic.2013.44
|View full text |Cite
|
Sign up to set email alerts
|

Nudging through Technology: Choice Architectures and the Mobile Information Revolution

Abstract: The information revolution has radically changed the way we make decisions and has expanded into mobile devices capable of informing choices at the point at which they are made. However, it is arguable whether the explosion of available information helps or hinders decision making, including in important domains such as healthcare and sustainability. Improving on that is the domain of choice architecture, intended to provide decision-knowledge through understanding choiceimplications and so guiding actions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This final topic builds upon the work of [5]. A major theme is Cloud Computing, which is a key enabling technology for much of the work discussed in this paper.…”
Section: Introductionmentioning
confidence: 98%
“…This final topic builds upon the work of [5]. A major theme is Cloud Computing, which is a key enabling technology for much of the work discussed in this paper.…”
Section: Introductionmentioning
confidence: 98%
“…In future it may also be possible to incorporate biomedical monitoring of depression-markers into such emotive-networks which could allow laboratory experimentation on virtual models of depression processes. This also provides potential for wider processing of depression-context data in parallel, grid and cloud computing systems which potentially may then also provide a means to accurately and effectively nudge patient behaviour, to both prevent and mitigate depressive episodes and symptoms; space limitations restrict a detailed exposition on the topic however a detailed discussion by Thomas et al can be found in (A. M. Thomas, Parkinson, et al, 2013).…”
Section: Technological Patient Monitoringmentioning
confidence: 99%
“…With increased access and bandwidth of cellular networks, information can now be uploaded, integrated, and processed on a massive scale. This allows rapid computation to help reduce perceived complexity and distraction through 'intelligent' software agents that tailor available options (Thomas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%